Pencetakan Injeksi Nylon PA66 Roda Gigi Pompa Minyak Motor 100cm3, Tahun 2004, Kapasitas 10 Biji/Jam - Ricky Ibrahim Mubarok; Syamsul Hadi; Anggun Novita Sari; Prayogi Adi Asmara; Yahya Dwiatma Wiyoga (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2026)
The 100 cm3 motorcycle oil pump gear spare parts are no longer produced by the factory in 2004, so consumers have difficulty obtaining them as a problem faced. The purpose of printing is to obtain 100 cm3 motorcycle oil pump gear spare parts that match the original specifications. The printing method includes: 100 cm3 motorcycle oil pump gear design, 100 cm3 motorcycle oil pump gear mold design, selection of plastic material from Nylon PA66, injection of Nylon PA66 into the 100 cm3 motorcycle oil pump gear mold at a temperature of 260°C, a pressure of 80 MPa, an injection holding time of 5 seconds, a cooling duration of 25 seconds, product release from the mold, mold channel cutting and finishing, and quality and dimensional inspection. The printing results are in the form of a 100 cm3 motorcycle oil pump gear with 25 teeth, a diameter of 53 mm, a thickness of 13 mm, and a bolt hole diameter of 6 mm with a dimensional tolerance of IT8, a surface roughness of Ra 1.2 µm, a total production cost of IDR 70,000,-/unit, and a process duration of 360 seconds/unit which implies that the 100 cm3 motorcycle, year 2004 can be re-functioned or can still operate with the supply of spare parts available according to the original specifications.